Analysis of regulatory implementation of regulation 536/2014 by European Union countries and Ukraine regarding the examination of clinical trials data and information - Liliia Hala; Oleksandr Nabok (Pensoft Publishers, 2024)
The article presents the results of a comparative analysis of regulatory requirements for expertise of clinical trials documentation, submitted for regulatory authority and ethic committees' approval in EU member countries and Ukraine, outlining the main trends, considering the updated Regulation (EU) No 536/2014, which came into effect on January 31, 2023. Among the positive changes are simplification of safety reporting requirements, use of artificial intelligence in the process of clinical trials documentation examination for obtaining regulatory authority and ethic commission approval, introduction of a single portal for submitting materials for clinical trials, and functioning of database for the submission and review of initial Clinical Trial Application documents and obtaining authorization within the EU to facilitate the interaction between applicants and regulatory authority are highlighted. To harmonize Ukraine's regulatory requirements with EU legislation, it is advisable to use a single portal for data exchange and document submission for applicants in regards to clinical trials, regulatory authority and local ethics committees. This will expedite the examination process of clinical trial documentation and simplify the monitoring of document review progress.